Household Energy Access for Cooking and Heating : Lessons Learned and the Way Forward - Ekouevi, Koffi; Tuntivate, Voravate (Washington, DC: World Bank, 2012)
Half of humanity about 3 billion people are still relying on solid fuels for cooking and heating. Of that, about 2.5 billion people depend on traditional biomass fuels (wood, charcoal, agricultural waste, and animal dung), while about 400 million people use coal as their primary cooking and heating fuel (UNDP and WHO 2009). The majority of the population relying on solid fuels lives in Sub-Saharan Africa and in South Asia. In some countries in Central America and in East Asia and the Pacific, the use of solid fuels is also significant. The inefficient and unsustainable production and use of these fuels result in a significant public health hazard, as well as negative environmental impacts that keep people in poverty. Strategies to improve energy access to the poor have focused mainly on electricity access. They have often neglected non electricity household energy access. It is, however, estimated that about 2.8 billion people will still depend on fuel wood for cooking and heating in 2030 in a business-as-usual modus operandi (IEA 2010). The need for urgent interventions at the household level to provide alternative energy services to help improve livelihoods is becoming more and more accepted. This report's main objective is to conduct a review of the World Bank's financed operations and selected interventions by other institutions on household energy access in an attempt to examine success and failure factors to inform the new generation of upcoming interventions. First, the report provides a brief literature review to lay out the multidimensional challenge of an overwhelming reliance on solid fuels for cooking and heating. Second, it highlights how the Bank and selected governments and organizations have been dealing with this challenge. Third, it presents lessons learned to inform upcoming interventions. And finally, it indicates an outlook on the way forward.